2006
DOI: 10.1186/cc4948
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fluid resuscitation on renal microvascular PO2 in a normotensive rat model of endotoxemia

Abstract: Introduction Septic renal failure is often seen in the intensive care unit but its pathogenesis is only partly understood. This study, performed in a normotensive rat model of endotoxemia, tests the hypotheses that endotoxemia impairs renal microvascular PO 2 (µPO 2 ) and oxygen consumption (VO 2,ren ), that endotoxemia is associated with a diminished kidney function, that fluid resuscitation can restore µPO 2 , VO 2,ren and kidney function, and that colloids are more effective than crystalloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Using oxygen-sensitive phosphorescent dyes in the first 1–4 hrs after LPS, Johannes, et al, and Dyson et al, have found that oxygen consumption falls during endotoxemia, albeit not significantly so compared to control animals 12, 13 .…”
Section: Energy Metabolism Solute Transport and Sepsismentioning
confidence: 99%
“…Using oxygen-sensitive phosphorescent dyes in the first 1–4 hrs after LPS, Johannes, et al, and Dyson et al, have found that oxygen consumption falls during endotoxemia, albeit not significantly so compared to control animals 12, 13 .…”
Section: Energy Metabolism Solute Transport and Sepsismentioning
confidence: 99%
“…This allows for the measurement of oxygen tension (PO 2 ) in the microcirculation [5,6] or interstitium [7,8], depending on the site of injection. The oxygen tension (PO 2 ) can be calculated from the phosphorescence decay kinetics.…”
Section: Biophotonicsmentioning
confidence: 99%
“…Furthermore, in a clinical study by Spargias et al , iloprost was successfully used to prevent contrast-mediated nephropathy 9. However, in these studies that reported iloprost to be a renoprotective agent, the selected doses were as low as 1–2 ng/kg/min and the infusion period lasted approximately four to six hours to avoid systemic hypotension, and dosing was not repeated 9,17-19…”
Section: Discussionmentioning
confidence: 99%